Spent coffee grounds: A sustainable approach toward novel perspectives of valorization. Issue 8 (12th May 2022) - Bijla, Laila; Aissa, Rabha; Laknifli, Abdellatif; Bouyahya, Abdelhakim; Harhar, Hicham; Gharby, Said
Abstract: Coffee is one of the most popular and preferred drinks in the world, being consumed for its refreshing and energizing properties. As a result, the consumption of coffee generates millions of tons of waste, in particular, spent coffee grounds (SCG). On the contrary, food waste recovery is an incredibly sustainable and convenient solution to the growing need for materials, fuels, and chemicals. SCG has been developed as a precious resource of several high value‐added products (oil, proteins, minerals, fatty acids, sterols….). Thus, a transformative pathway to a circular economy that involves the valorization of coffee wastes and by‐products is currently attracting the attention of researchers worldwide. The potential growth of scientific papers and publications promotes a comprehensive review to determine the research hotspots, knowledge structure, and to consider future avenues and challenges. Therefore, in this paper, we conducted a systematic review based on 275 indexed papers on the composition and valorization of SCG as a prospective environmental source. Practical applications: SCG can be applied in agro‐food industries. Abstract : In the graph, coffee consumption generates large quantities of spent coffee grounds, the unused part of the coffee bean that is left after brewing. However, due to its composition, this waste stream has the potentially to be valorized and converted into several valuable bioproducts such as biopolymers, biofuels and filter materials, instead of being discarded in landfills.